2018
DOI: 10.1021/acs.est.8b00672
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impacts of Biochars on Urease Activity: High pH, Heavy Metals, Polycyclic Aromatic Hydrocarbons, or Free Radicals?

Abstract: Although biochars show promise for soil remediation, their negative impacts have not been systematically assessed. This study investigated the effects of corn cob biochars on ureasemediated urea hydrolysis and attempted to determine the mechanisms underlying those effects. The results showed that biochars inhibited urease activity (indicated by the NH 4 + generation). Released heavy metals and polyaromatic hydrocarbons explained the 20% inhibition of urease activity in biochar supernatants (200 °C) but could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Whether EPFRs in wildfire charcoal do indeed pose an environmental risk remains unclear, and the rate of ROS production from EPFRs in field aged wildfire charcoal will be an important area for future research. Even at low concentrations, EPFR-derived ROS in environmental systems may influence ecosystem functions including organic matter transformation 42 , plant germination 15,16 , aquatic algal growth 43 , and enzymatic activity 17 , as well as having adverse effects on bacteria 19 and invertebrates 20,21 . Wildfires are a natural, necessary and frequent disturbance in many of the world's ecosystems 44 .…”
Section: Epfr Abundance Depends On Carbonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether EPFRs in wildfire charcoal do indeed pose an environmental risk remains unclear, and the rate of ROS production from EPFRs in field aged wildfire charcoal will be an important area for future research. Even at low concentrations, EPFR-derived ROS in environmental systems may influence ecosystem functions including organic matter transformation 42 , plant germination 15,16 , aquatic algal growth 43 , and enzymatic activity 17 , as well as having adverse effects on bacteria 19 and invertebrates 20,21 . Wildfires are a natural, necessary and frequent disturbance in many of the world's ecosystems 44 .…”
Section: Epfr Abundance Depends On Carbonizationmentioning
confidence: 99%
“…1). EPFRs containing particles have thus been linked to adverse impacts on biological systems, including inhibition of plant germination 15,16 , reduced enzymatic activity 17 , cytotoxicity to single cells 18 , toxic effects on both bacteria 19 , and aquatic invertebrates 20,21 . Therefore, the presence of EPFRs in charcoal and the subsequent formation of ROS may lead to yet unexplored effects on ecosystem functions and human health.…”
mentioning
confidence: 99%
“…For example, biochar is often known as a "super-sorbent"; however, most of this considerable progress regarding adsorption using biochar was conducted at lab scale with batch sorption (Alam et al 2018a, b;Cao et al 2009;Chen et al 2008Chen et al , 2012b. Direct applications of biochar particles will inevitably release fine particles (at the size of nm to μm) into the environment, which may cause potential risk to human beings and the ecosystem (Lian and Xing 2017;Liu et al 2018b;Zhang et al 2019). Considering the special properties of biochar, to minimize environmental transport and the associated risks for safe applications is essential, biochar particles can be functionalized and incorporated into devices or engineered treatment facility.…”
Section: Introductionmentioning
confidence: 99%
“…However, others biochar studies have found opposite responses. Liu et al, reported decreased urease activity in biochar amended soils, likely the result of oxidative reactions with free radicals on biochar surfaces [56]. Huang et al, utilized rice straw biochar (5%, w:w), observing a decrease in urease and alkaline phosphatase activities [57].…”
Section: Biochar Effects On Soil Enzyme Activity and Microbial Diversitymentioning
confidence: 99%